Determination of Curdlan Oligosaccharides with High-Performance Anion Exchange Chromatography with Pulsed Amperometric Detection - Lidong Cao; Huifang Tian; Miaomiao Wu; Hongjun Zhang; Puguo Zhou; Qiliang Huang (Journal of Analytical Methods in Chemistry)
The increasing interest of curdlan oligosaccharides (COS) in medicine and plant protection fields implies a necessity to identify and quantify this product. In the present study, an efficient and sensitive analytical method based on high-performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD) was established for the simultaneous separation and determination of D-glucose and ß-1,3-linked COS ranging from (COS)2 to (COS)6 within 20 min. Detection limits were 0.01 to 0.03 mg/L. The optimized assay was performed on a CarboPac-PA100 analytical column (4 mm × 250 mm) using isocratic elution with water−0.2 M sodium hydroxide−0.5 M sodium acetate mixture (50 : 30 : 20, v/v/v) as the mobile phase at a flow rate of 0.8 mL/min. Regression equations indicated a good linear relationship (R2 = 0.9992–1.0000, n = 6) within the test ranges. Quality parameters including precision and accuracy were fully validated and found to be satisfactory. More important, the regression of natural logarithm values of retention times (log10 RT) versus the degree polymerization (DP), as well as the slope coefficient of each COS’s linear equation versus the corresponding DP, fitted a linear relationship well. These inherent linear relationships could provide valuable information to tentatively identify and quantify the COS even with the DP more than 6 without authentic standard. Furthermore, when the log10 RT was plotted against log10 flow rate for each COS, a perfect linear relationship was also observed.